2016
DOI: 10.1007/s10552-016-0755-0
|View full text |Cite
|
Sign up to set email alerts
|

An update of the WCRF/AICR systematic literature review on esophageal and gastric cancers and citrus fruits intake

Abstract: PurposeThe 2007 World Cancer Research Fund/American Institute for Cancer Research expert report concluded that foods containing vitamin C probably protect against esophageal cancer and fruits probably protect against gastric cancer. Most of the previous evidence was from case–control studies, which may be affected by recall and selection biases. More recently, several cohort studies have examined these associations. We conducted a systematic literature review of prospective studies on citrus fruits intake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…For example, H. pylori infection has been well recognized to be a significant risk factor of GNCC, while the association between H. pylori and cardia gastric cancer incidence remains unclear . Moreover, smoking, intake of salty, preserved meat and smoked food are risk factors of GNCC, while low citrus fruit intake, gastroesophageal reflux disease (GERD) and obesity have been suggested to be associated with higher GCC risk . In the current meta‐analysis, the pooled OR for the association between IM and GNCC was 4.98, which is higher compared with GCC (pooled OR = 1.93).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, H. pylori infection has been well recognized to be a significant risk factor of GNCC, while the association between H. pylori and cardia gastric cancer incidence remains unclear . Moreover, smoking, intake of salty, preserved meat and smoked food are risk factors of GNCC, while low citrus fruit intake, gastroesophageal reflux disease (GERD) and obesity have been suggested to be associated with higher GCC risk . In the current meta‐analysis, the pooled OR for the association between IM and GNCC was 4.98, which is higher compared with GCC (pooled OR = 1.93).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer remains one of the most common malignancies in both sexes, and is the third leading cause of cancer mortality worldwide . Helicobacter pylori ( H. pylori ) has been well recognized as the most important risk factor for gastric cancer, moreover, smoking and dietary factors such as high intake of salty food, preserved meat and alcohol, and low citrus fruit consumption are also associated with higher gastric cancer risk . The survival rate for patients with gastric cancer remains poor, which is associated with the late stage of diagnosis.…”
mentioning
confidence: 99%
“…In several observational studies, non-frequent consumption of fresh fruits and vegetables is closely associated with a higher risk of ESCC 17-21 . However, in that report, no distinction was made between ESCC and esophageal adenocarcinoma.…”
Section: Risk Factors Of Esccmentioning
confidence: 99%
“…More recently, different meta-analyses have highlighted an inverse association between CF intake and the risk of various types of cancers, such as breast cancer [274], bladder cancers [275,276,277], and esophageal cancer [278]. A very recent systematic literature review of prospective studies on CF intake and risk of esophageal and gastric cancers revealed only a marginally significant decreased risk of esophageal cancer and reported no significant inverse association for gastric cardia cancer, but data are still limited [279]. …”
Section: Epidemiological Studiesmentioning
confidence: 99%